Analytical study to assess the level of commitment of some referees of the Collegiate Games - AL-NUAIMI, SAWSAN JADDOA KADHIM (International Journal of Psychosocial Rehabilitation, 2020)
As a result of the scientific development that the world is currently witnessing and in various fields, and the effects that accompany it, in addition to the psychological conflict between the individual and society to reach what he aspires to, the psychological factor has become a factor affecting the individual’s performance towards failure and success. Indeed, psychology is now one of the important sciences that It needs to study and delve into the depth of its many vital influences, and therefore psychological numbers entered the field of sports similar to the technical and physical numbers after officials and coaches were convinced of its usefulness towards reaching higher levels, as it became a science for the coaches, players, administrators and referees to benefit from, so that some of them give priority to the arrangement As, "The results of a recent study conducted on a large sample of athletes showed that the psychology of sport is at the forefront of the sciences that aid the success and development of the level of athletic performance.